Նոր Գիրք «Իսահակ Ալավերդյան» - Մովսիսյան, Արմինե
В этой статье рассматривается и оценивается работа доктора филологических наук, профессора Сократа Ханяна „Исаак Алавердян”. Отмечается, что автор работы тщательно изучая богатое литературное наследие прозаика, драматурга, театроведа, переводчика, педагога Исаака Алавердяна, создал ценное исследование, которое можно считать знаменательным явлением в процессе изучения современной армянской литературы. The article considers and evaluates Doctor of Philology and professor Sokrat Khanyan's work “ Isahak Alaverdyan”. It is mentioned in the article that the author of the work has cveated a valuable research by thorougly studying the literary rich heritage of the prose writer, playwright, theatrical expert, translator and teacher Alaverdyan. This can be considered as a significant phenomenon in the history of modern Armenian literature study.
Keywords: Գրականագիտություն